The role of task repetition in a Korean as a foreign language classroom: Writing quality, attention to form, and learning of Korean grammar - Kim, YouJin; Kang, Sanghee; Yun, Hyunae; Kim, Binna; Choi, Bumyong (Foreign language annals, 2020)
Task repetition is being increasingly examined in the fields of second language acquisition and task‐based language teaching, and the findings have revealed insightful theoretical and pedagogical implications for foreign language instruction. However, previous research has mainly focused on speaking tasks, and the role of different types of task repetition using collaborative writing tasks has received little attention. This study compared two task repetition types (exact task repetition and procedural repetition) on the quality of writing output (i.e., complexity and accuracy), learner attention to linguistic forms, and the learning of four Korean grammar features. Thirty‐eight Korean‐language learners were assigned to either an exact task repetition or a procedural repetition condition. They completed a pretest, two collaborative writing tasks, and a posttest over two weeks. Written output was analyzed for complexity and accuracy, and learners' oral interactions during collaborative writing were analyzed for the occurrence of language‐related episodes. Pretest and posttest responses were scored for suppliance and accuracy of target feature production. Results showed that exact task repetition benefitted syntactic complexity and the accuracy of target features. However, little evidence of benefits for global accuracy was found. The procedural repetition group performed less well during the second task performance than they did on the first task. However, they scored significantly higher on the posttest compared to the exact repetition group. The Challenge “Let's do it again.” When instructors design and implement tasks, they often wonder, “Would it be useful for students' language learning if some parts of previous tasks are repeated?” The current study examined the effects of task repetition on students' writing output, peer interaction, and grammar learning through collaborative task performance among beginner‐level Korean‐language learners.